A Multidimensional Model of Religiosity from Adolescence through the Transition to Adulthood - Hayward, George M. (Journal for the scientific study of religion, 2021)
While many multidimensional models of religiosity have been proposed over the years across a range of samples, nearly all are cross-sectional; this prohibits the assessment of model change or stability over time, particularly with regard to developmental changes at critical junctures in the life course. Recently, a longitudinal, five-dimensional model of religiosity during adolescence was proposed and validated, making significant progress in this regard. This research note now attempts to replicate this model on the young adult sample from the same study. Using data from the National Study of Youth and Religion, results show support for a modified version of this typology over time––one that combines the two dimensions of religious practice and incorporates a number of cross-loadings between dimensions. Importantly, this model fits well across both adolescence and young adulthood, lending strong support for these four dimensions of religiosity, their indicators, and their persistence as valid measures across a decade of developmental change.